Exploring Effective Strategies for the Control of Gray Mold Disease in Tomatoes Caused by Botrytis using Bacterial Bioagents: Control of Gray Mold Disease in Tomatoes - Rahman, Mosaddekur; Almasoudi, Najeeb; Abo-Elyousr, Kamal; Asiry, Khaled (Journal of King Abdulaziz University-Meteorology Environment and Arid Land Agriculture Sciences, 2025)
Gray mold disease, caused by Botrytis cinerea, is a significant threat to tomato crops, leading to severe yield losses globally. Traditional chemical control methods pose environmental hazards and the potential for pathogen resistance, highlighting the need for sustainable alternatives. This review explores the use of bacterial bioagents as an eco-friendly and effective strategy for controlling gray mold in tomatoes. Key bacterial strains, such as Bacillus, Pseudomonas, and Streptomyces, have demonstrated promising biocontrol properties, including antifungal activity, competition for nutrients, and induction of plant defense mechanisms. The mechanisms through which these bacteria inhibit Botrytis involve the production of secondary metabolites, lytic enzymes, and volatile organic compounds (VOCs). Field trials and greenhouse studies have shown variable success, depending on environmental conditions, bioagent strain selection, and application methods. Integrated management practices combining bacterial bioagents with cultural and agronomic practices further enhance the efficacy of disease control. The study concludes that bacterial bioagents represent a viable and sustainable approach to managing gray mold in tomatoes, though further research is needed to optimize their use and scalability in commercial agriculture.